(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The dynamics of the share of household expenditures in GDP has deteriorated over the years, indicating that threatening economic processes occurring in the structure of the Ukrainian economy. To overcome this situation, it is necessary to find mechanisms for overcoming the threats to Ukraine’s economic security, which in this case are related to the activities of the main domestic economic investor of the state - the household and its interaction with the branches of production and services. One of the possible and productive approaches to addressing the pressing issues is the cognitive modeling of household development. The cognitive model of self-organization of the activity of households in Ukraine based on the evaluation of the links between the factors characterizing the processes of interaction between households and the branches of the economy provides an opportunity to assess the degree of risk decision-making aimed at efficient management of the costs of final consumption of households.